2006
DOI: 10.1159/000094138
|View full text |Cite
|
Sign up to set email alerts
|

The Sodium Channel of Human Excitable Cells is a Target for Gambierol

Abstract: Background: Gambierol is a polycyclic ether toxin with the same biogenetic origin as ciguatoxins. Gambierol has been associated with neurological symptoms in humans even though its mechanism of action has not been fully characterized. Methods: We studied the effect of gambierol in human neuroblastoma cells by using bis-oxonol to measure membrane potential and FURA-2 to monitor intracellular calcium. Results: We found that this toxin: i) produced a membrane depolarization, ii) potentiated the effect of veratrid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
49
1

Year Published

2007
2007
2010
2010

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(53 citation statements)
references
References 52 publications
3
49
1
Order By: Relevance
“…The discrepancy between the lack of effect on most cloned Na v channels as observed in our oocyte experiments with the effect described on sodium channels in human neuroblastoma cells and cerebellar granule neurons (Louzao et al, 2006) might be explained as follows: the block of K v channels most likely contributes to a depolarization of the membrane. This gives a lowering of the action potential threshold and leads to a more easy activation of Na v channels.…”
Section: Discussioncontrasting
confidence: 86%
See 2 more Smart Citations
“…The discrepancy between the lack of effect on most cloned Na v channels as observed in our oocyte experiments with the effect described on sodium channels in human neuroblastoma cells and cerebellar granule neurons (Louzao et al, 2006) might be explained as follows: the block of K v channels most likely contributes to a depolarization of the membrane. This gives a lowering of the action potential threshold and leads to a more easy activation of Na v channels.…”
Section: Discussioncontrasting
confidence: 86%
“…Compounds such as gambierol are described to be produced by G. toxicus dinoflagellates, but relatively little is known about their targets. Although sodium and potassium channels have been proposed in the literature as possible targets (Inoue et al, 2003;Ghiaroni et al, 2005;Louzao et al, 2006), very few papers can couple these targets to the intoxication symptoms (Cameron, 1993). In this article, we define VGPCs as a physiological target of gambierol, examine its selectivity and speculate on gambierol's role in CFS intoxications.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Inasmuch as we have previously shown that brevetoxin-induced Ca 2ϩ influx is triggered by the activation of VGSCs, it is reasonable to infer that gambierol is not an activator of VGSC in CGNs. In contrast to these results, a recent report has found that gambierol produced a modest, relative to veratridine, increment in Ca 2ϩ influx in neuroblastoma cells (Louzao et al, 2006). Based on the results of pharmacological experiments, these authors concluded that gambierol acts as a partial agonist at neurotoxin site 5 of the VGSC.…”
Section: Gambierol Antagonism Of Sodium Channelsmentioning
confidence: 86%
“…Also, high concentrations of gambierol (30 μM) were reported to produced Na + -dependent membrane depolarisation, potentiated the effect of veratridine, decreased P-CTX-3C-induced depolarisation and increased cytosolic Ca 2+ concentration in human neuroblastoma cells (Louzao et al 2006). Interestingly, the membrane depolarisation caused by gambierol was partially blocked by neosaxitoxin, a well known Na + -channel blocker.…”
Section: Gambierol and Polyether Toxinsmentioning
confidence: 99%